2021
DOI: 10.3390/educsci11100569
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Working in Special Schools in Scotland Acting with Practical Wisdom: Supporting Children with Additional Needs in COVID-19 Lockdown

Abstract: The COVID-19 lockdown has substantially disrupted the established facets of teacher engagement with their students, and, given the significance of this multidimensional interaction, it brings into question what we know as teachers’ identity. The lockdown has offered a dilemmatic context where the processes of teaching and learning and being(s) a teacher are being re-visited and re-negotiated. This paper looks specifically at the perceptions of two teachers of their lockdown experience working within a special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…The result supports the importance of supplies in the success of the instruction as it was highlighted during the bond paper drive conducted all over the Philippines to sustain the different learning modules relevant to the use of self-learning modules (Rappler, 2020). The statement of one of the SPED teachers corroborates the findings of Mercieca et al (2021) that SPED teachers created relevant decisions or judgments at precisely those moments where guidelines and procedures are unclear, and the criteria open to multiple interpretations. The result supports Formoso (2019) when the respondents in her research also reported that they were mostly challenged by their lack of knowledge and trainings on the proper conduct of SPED but opposed the shortage of material resources.…”
Section: Resultssupporting
confidence: 67%
“…The result supports the importance of supplies in the success of the instruction as it was highlighted during the bond paper drive conducted all over the Philippines to sustain the different learning modules relevant to the use of self-learning modules (Rappler, 2020). The statement of one of the SPED teachers corroborates the findings of Mercieca et al (2021) that SPED teachers created relevant decisions or judgments at precisely those moments where guidelines and procedures are unclear, and the criteria open to multiple interpretations. The result supports Formoso (2019) when the respondents in her research also reported that they were mostly challenged by their lack of knowledge and trainings on the proper conduct of SPED but opposed the shortage of material resources.…”
Section: Resultssupporting
confidence: 67%
“…The situation is exacerbated by the fact that low-income families and students have limited access to the technology essential for online learning (Radina & Balakina, 2021). The overarching theme also prompted researchers to look into teachers' ability to provide remote special education (Mercieca et al, 2021;Jurčević and Kudek, 2021). Due to the investigation, teachers found it challenging to handle the basic requirements of online learning.…”
Section: Literature Reviewmentioning
confidence: 99%